Investigation of applying dampers in elevated water tanks using time-history analysis - Rajaie, Ehsan (International Journal of Engineering and Technology, 2015)
In this paper, the dynamic behavior of water storage tanks in investigated. Using time-history analysis based on three major earthquakes, the performance of system is illustrated. Two conditions, first with damper and second with no damper are presented and the relevant results are compared. The main results consist of base shear forces and also maximum target displacements.Â